Analisis Senyawa Piren pada Alga Laut Eucheuma cottoni Di Perairan Kabupaten Bantaeng - Yusuf, Evana Y.; La Nafie, Nursiah; Dali, Seniwati (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2016)
The compounds pyrene is one of the polycyclic aromatic hydrocarbons (HAP) which is derived from petroleum. These compounds are carcinogenic and toxic for the marine biota. The purpose of this study to determine the levels of pyrene compounds in marine algae. In this research, analysis of pyrene compounds in marine algae Eucheuma cottonii using the method of GC - MS (Gas Chromatography - Mass spectrophotometry). Sampling was conducted in the waters the Bantaeng Regency with a 6 point sampling different locations namely Nipa-nipa, Bakara, Boroloe, Tapaloe, Baruga village and Baruga. The results showed that the concentration of pyrene compounds found in marine algae Eucheuma cottonii at 6 locations in waters the Bantaeng Regency has a concentration low enough pyrene compounds that is 0009-0063 ppm. This means that the concentration of pyrene was obtained below the threshold value determined by the decision of national of Environmental ministry for the marine life.